Silicon nanoparticles enhance maize yield and water productivity via regulating photosynthesis and canopy structure under mild regulated deficit irrigation - Liang, Xukai; Liao, Qi; Guo, Panpan; Yang, Ziyi; Kang, Shaozhong; Du, Taisheng; Tong, Ling; Ding, Risheng (Frontiers in Plant Science, 2026)
IntroductionSilicon nanoparticles (SiNPs) effectively mitigate drought stress in crops, yet their physiological mechanisms in maize remain unclear.MethodsThis study conducted field experiments in the arid region of northwest China, setting up three maize genotypes (Zhengdan 958, Zhongdan 2, and MC670), two irrigation methods (full irrigation, FI, and regulated deficit irrigation, RDI), and two exogenous treatments (water as control, and SiNPs application).ResultsThe RDI increased stomatal density (SD), intrinsic water use efficiency (iWUE), and water productivity (WP), albeit with a slight reduction in yield. However, the application of SiNPs increased the yield and WP across all three genotypes under both FI and RDI. Additionally, SiNPs notably enhanced SPAD values, stomatal conductance (gs), net photosynthesis rate (A), leaf area index (LAI), and the fraction of photosynthetically active radiation (fPAR), while reducing the leaf inclination angle (LIA) at the middle ear position. Further analysis revealed the following mechanisms: (1) an increase in SPAD and gs enhanced A; (2) enhanced LAI and reduced LIA at the ear-bearing canopy layers significantly improved fPAR; and (3) the combined increase in A and fPAR synergistically contributed to increased maize yield. The improvements in WP were more strongly correlated with yield gains than with changes in evapotranspiration.DiscussionThe findings demonstrate that SiNPs improve maize productivity and water use efficiency under both full and deficit irrigation by coordinately enhancing photosynthetic performance and optimizing canopy light interception. The results provide physiological insights into how SiNPs alleviate drought-related limitations in maize. These findings offer important theoretical insights and a practical strategy for employing SiNPs as a sustainable crop enhancer under water-limited conditions.